Rancangan Membangun Desa Mandiri dengan Pemetaan Potensi Desa : Studi pada Desa Kanigoro Kabupaten Gunungkidul - Bambang Sulistyono; Ilham Ahmad; Dinda Ariyanti; Livanda Putri; Alinsya Pangistia; Shinta Falasifa; Raihan Nur; Daffa Dhiya; Annissa Salsabilla; Queennniken Yuliana; Suci Elhawa (Universitas Muhammadiyah Manado, 2024)
One of the advanges of an island nation is possessing abundant natural resource potentials. Kanigoro Village which located at Kapanewon Saptosari, Gunung Kidul is a kind of village that has many natural resource potentials. To maximize the natural resource potentials in Kanigoro Village, field study students of Sebelas Maret University plan to create a village potential mapping. Implemented Methods of field study program involve some activities such as students provision, location placement, and implementation of program. Facilities located at Kanigoro Village are sufficient to provide it’s living such as formal and nonformal education, health facilities, government facilities such hall village to anticipate disasters for example tsunami and landslide. In general, it is also explained that the education level of the people of Kanigoro village is relatively high. Kanigoro Village possess a huge potential in tourism and culture. Those huge potential need to be improved as an attraction in order to attract tourists to visit Kanigoro Village.